Extra-Gingival Pyogenic Granuloma Displacing Teeth - Dal Prá, Ketelin Juliane [UNESP]; Bernabé, Daniel Galera [UNESP]; Miyahara, Glauco Issamu [UNESP]; Biasoli, Eder Ricardo [UNESP]; Crivelini, Marcelo MacEdo [UNESP]; Tjioe, Kellen Cristine [UNESP] (Wolters Kluwer, 2017)
Pyogenic granuloma is a common cause of growth of soft tissue in the oral cavity, especially in the gingiva. It is mainly associated with local and chronic irritants besides hormonal changes during pregnancy. Here, the authors present an unusual patient of an extra-gingival pyogenic granuloma with large dimensions and displacing teeth arising in a male patient. This is an interesting patient to be reported due to its exacerbated and atypical clinical features.
Keywords: Granuloma; lip; mouth; pyogenic; soft tissue injuries